2021
DOI: 10.3389/fmicb.2021.770591
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixing Garlic Skin on Fermentation Quality, Microbial Community of High-Moisture Pennisetum hydridum Silage

Abstract: Garlic skin, a by-product of garlic processing, was supposed to improve the fermentation quality of high-moisture silages because of its low moisture content and active compounds. Thus, fermentation and microbial characteristics of high-moisture Pennisetum hydridum ensiled with the addition of 0, 10, 20, and 30 wt% garlic skin (on a fresh matter basis) were analyzed during a 60-days fermentation. Results showed that the addition of garlic skin increased the dry matter content and lactic acid production, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This is in line with another study in which the LA and AA levels decreased in silage as the proportion of pistachio hulls increased [29]. Chen et al [30] reported that a low moisture content is detrimental to LA accumulation. This can be attributed to the reduced activity of the bacteria in a low-moisture environment, resulting in a lower concentration of fermentation acid [31].…”
Section: Effects Of the Mixing Proportion And Lactic Acid Bacteria Ad...supporting
confidence: 89%
“…This is in line with another study in which the LA and AA levels decreased in silage as the proportion of pistachio hulls increased [29]. Chen et al [30] reported that a low moisture content is detrimental to LA accumulation. This can be attributed to the reduced activity of the bacteria in a low-moisture environment, resulting in a lower concentration of fermentation acid [31].…”
Section: Effects Of the Mixing Proportion And Lactic Acid Bacteria Ad...supporting
confidence: 89%
“…Accordingly, a recent report demonstrated that supplementation of garlic skin improved the growth performance of lambs by altering the ruminal bacterial composition by increasing the relative abundances of certain genera while decreasing others [37]. Garlic skin also improved the fermentation quality of high-moisture silages by increasing the abundance of Lactobacillus and decreasing the relative abundance of Clostridium [38]. Notably, although garlic peels and cloves displayed different effect on microbial growth, all parts of the bulb inhibited microconidia germination and hyphae branching of the pathogenic fungus Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most metabolic categories increased over time, which indicates that the metabolic intensity of the microbial community increased as microbial diversity and abundance increased ( Qiu et al, 2018 ). High abundances of beneficial microorganisms were detected in the LAB treatments, which are the primary factors causing these types of metabolism to be active ( Chen J. et al, 2021 ; Du et al, 2021 ). In addition, the high amino acid biosynthesis activity indicates that adding LAB allows macromolecular proteins present in the silage to be degraded into amino acids or peptides that are easily absorbed by the body ( Du et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%